Polymyalgia rheumatica and rheumatoid arthritis of the elderly: a clinical, laboratory, and scintigraphic comparison. Issue 9 (September 1991) - Häntzschel, H; Bird, H A; Seidel, W; Krüger, W; Neumann, G; Schneider, G; Wright, V
Abstract : Clinical, laboratory, and scintigraphic features of 16 patients with polymyalgia rheumatica and 23 patients matched for age presenting with classical or definite rheumatoid arthritis (American Rheumatism Association 1958 criteria) of the elderly were compared in order to define features that might distinguish between these two syndromes. The sensitivity of proposed diagnostic criteria for polymyalgia rheumatica was always higher in the group with polymyalgia rheumatica, though only significantly so for morning stiffness. A comparison of 27 different laboratory features showed few significant differences between the diseases, though correlation between laboratory variables within each of the disease groups differed, perhaps suggesting a fundamental pathogenetic difference between them. Scintigraphy of the shoulder joint proved of no value in differential diagnosis. It was concluded that polymyalgia rheumatica and rheumatoid arthritis of the elderly are probably discrete clinical entities. Bilateral upper arm tenderness, lack of positive rheumatoid factor, and a normal caeruloplasmin are the most valuable features for distinguishing polymyalgia rheumatica from rheumatoid arthritis of the elderly.